2018
DOI: 10.1080/00207179.2018.1548773
|View full text |Cite
|
Sign up to set email alerts
|

On the use of Youla–Kucera parametrisation in adaptive active noise and vibration control – a review

Abstract: Youla-Kucera parametrization plays a very important role in adaptive active vibration control and adaptive active noise control. This concerns both vibration and noise attenuation by feedback as well as by feedforward compensation when a measurement of an image of the disturbance (noise or vibration) is available. The paper will review the basic algorithms and various extensions trying to emphasize the advantages of using Youla-Kucera parametrization. Specific aspects related to the use of this approach in ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…k,i ) which are Hurwitz ∀i, j. The coprime factors are computed at each vertex ν i using the statespace representations written in ( 6)- (7).…”
Section: Coprime Factorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…k,i ) which are Hurwitz ∀i, j. The coprime factors are computed at each vertex ν i using the statespace representations written in ( 6)- (7).…”
Section: Coprime Factorizationmentioning
confidence: 99%
“…The YK parameterization has been successfully applied to several domains such as: 1) Noise/vibration control [7]; 2) Interpolation between robust and high performance controllers [4]; and 3) Control systems subjected to convex constraints [3]. A significant literature review of YK work including its recent applications can be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, the use of YK parameter Q in noise and vibration rejection evolved from rejecting a known signal with a given frequency to variable known and unknown spectral characteristics. Different im plementations of the YK parameter Q are proposed according to the disturbance type Landau (2018) .…”
Section: Control Implementationmentioning
confidence: 99%
“…Then, the YK parameter Q is deduced to switch from the nominal controller to the updated one (see Section 3 ). In direct configuration, a tuning algorithm is developed to define design adaptive Finite Impulse Response (FIR) or Infinite Impulse Response (IIR) compensators as a YK parameter Q and update directly the controller that minimizes the residual noise Landau (2018) .…”
Section: Control Implementationmentioning
confidence: 99%
See 1 more Smart Citation